Pengaruh Penggunaan Aplikasi Quizizz terhadap Penguasaan Kosakata Bahasa Bugis Kelas VI UPT SD Negeri 8 Pangkajene Kabupaten Sidrap - Sri Wahyuni Suyuti; Syamsudduha Syamsudduha; Andi Fatimah Yunus (Universitas Negeri Makassar, 2026)
This study aims to determine students' mastery of Bugis vocabulary before and after using the Quizizz application and to determine the effect of this application on the vocabulary mastery of sixth-grade students at the UPT SD Negeri 8 Pangkajene, Sidrap Regency. This study was quantitative with a quasi-experimental approach using a One Group Pretest-Posttest design. The sample consisted of 25 students selected using a total sampling technique. Data collection techniques used pre-tests and post-tests, while data analysis was conducted using descriptive and inferential statistics using paired sample t-tests. The results showed that the average pre-test score was 64.16, categorized as sufficient, while the average post-test score increased to 94.00, categorized as very good. The hypothesis test results obtained a significance value <0.05, thus H₀ was rejected and H₁ was accepted. This indicates that there is a significant effect of using the Quizizz application on students' Bugis vocabulary mastery. Therefore, using the Quizizz application can improve students' Bugis vocabulary mastery and create more interactive and enjoyable learning.